PENGARUH STRESS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GANDA MADY INDOTAMA SUDIRMAN JAKARTA SELATAN - Larisa; Siamto, Wahadi (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the influence of leadership and motivation on the performance of employees of PT Aru Raharja, South Jakarta. The method used is a descriptive method with a quantitative approach. The sampling technique used is probability sampling, the sampling method using a saturated sample. Data analysis uses regression analysis, correlation coefficient analysis, coefficient analysis of determination and hypothesis testing. The results of this study are leadership (X1) and Motivation (X2) have a positive and significant effect on employee performance (Y) with the regression equation ???? = 10.748 + 0.642????1 + 0.223????2. The coefficient of determination has a simultaneous effect on 34.4%, the hypothesis test partially obtained a leadership number of 5.509 tcount> ttable (5,509> 1,673). Then H0 is rejected and H1 is accepted. This means that there is a positive and significant influence between independent variables, namely leadership (X1) on employee performance (Y). Motivation of ????Malccit> ????????????bre???? or (3,629> 1,673). Then H0 is rejected and H2 is accepted. This means that there is an influence between independent variables, namely motivation (X2) on employee performance (Y). Hypothesis test obtained Fcount value> Ftable value (13,904> 4.02). With H0 rejected and H3 is accepted, meaning leadership (X1) and Motivation (X2) together have a positive effect on employee performance (Y).